Asynchronous fracture of hierarchical microstructures in hard domain of thermoplastic polyurethane elastomer: Effect of chain extender. (28th February 2018) - Guo, Yaqian; Zhang, Ruoyu; Xiao, Qiang; Guo, Hongxia; Wang, Zongbao; Li, Xing; Chen, Jing; Zhu, Jin
Abstract: Four chain extenders, 1, 3-propanediol (PDO), 2-methyl-1, 3-propanediol (MPO), 2, 2-dimethyl-1, 3-propanediol (NPG) and 2, 2, 4, 4-tetramethyl-1, 3-cyclobutanedio (CBDO) are chosen to synthesize model polyurethanes, respectively. Although with similar oxygen distance between the two hydroxyl groups, their volumes increase gradually according to computer simulation. As expected, the degree of microphase separation decreases with the increasing chain extender volume. Except for CBDO based polyurethane, the other three samples show systematic variations in mechanical properties. Various techniques including single-molecule force spectroscopy (SMFS), small-angle X-ray scattering (SAXS) and Fourier transform infrared spectroscopy (FTIR) are employed to investigate the structural changes after tensile break in different length scales. A picture of asynchronous fracture of microstructures during the tensile break of thermoplastic polyurethane elastomers can be obtained by the combination of different analytical methods. It is interesting to note that the macroscopic break may not affect the state of hydrogen bonding or the hard phase network. Sometimes, the hydrogen bonding state changes a lot while the phase network keeps almost the same, or vice versa. Graphical abstract: Highlights: When the volume of chain extender increased, the microphase separation was depressed. The breakage of network and the hydrogen bonding association could be asynchronous. The increased intensity of hydrogen bonding didn't necessarily meant high recoverability.